2008
DOI: 10.1021/la7024846
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Ion-Mobility Characterization of SAM-Functionalized Au Nanoparticles

Abstract: We present results of a systematic examination of functionalized gold nanoparticles (Au-NPs) by electrospray-differential mobility analysis (ES-DMA). Commercially available, citrate-stabilized Au colloid solutions (10-60 nm) were sized using ES-DMA, from which changes in particle size of less than 0.3 nm were readily discerned. It was found that the formation of salt particles and the coating of Au-NPs by salt during the electrospray process can interfere with the mobility analysis, which required the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
137
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(148 citation statements)
references
References 29 publications
11
137
0
Order By: Relevance
“…and quantify surface coverage of single strand DNA molecules on 10 nm gold nanoparticles [65]. Similar studies have been reported for self-assembled alkane thiol monolayers (SAMs) on 10 and 60 nm AuNPs [15]. This study found that the coverage of SAMs was independent of the size of the AuNPs.…”
Section: Nanoparticle-biomolecule Conjugatessupporting
confidence: 78%
See 3 more Smart Citations
“…and quantify surface coverage of single strand DNA molecules on 10 nm gold nanoparticles [65]. Similar studies have been reported for self-assembled alkane thiol monolayers (SAMs) on 10 and 60 nm AuNPs [15]. This study found that the coverage of SAMs was independent of the size of the AuNPs.…”
Section: Nanoparticle-biomolecule Conjugatessupporting
confidence: 78%
“…This work was followed over the next decade by several reports from Allmaier et al [11], Wick et al [12] and de la Mora et al [13] related to characterization of several other proteins, viruses and polymers. Starting in 2006 as seen in Figures 1.3A and 1.3B a dramatic increase in the number of publications and citations related to ES-DMA occurred with contributions from Biswas et al [14], Zachariah et al [15], Loo et al [16], Hogan et al [17], Pergantis et al [18], Pease et al [19] and Hackley et al [20]. Although developed primarily for size determination, with an increasing pool of users, several orthogonal utilities have been found for this technique a detailed discussion of which will be appear later in Chapter 3.…”
Section: Growth Of Es-dmamentioning
confidence: 95%
See 2 more Smart Citations
“…Tsai et al 59 showed that gold nanoparticles (10-60 nm) coated with self-assembled monolayers (SAMs) of alkanethiols appeared to have a "soft" organic coating. The SAM/Au particle size deduced from the mobility measurements was smaller than the size expected from purely geometric considerations.…”
Section: Discussionmentioning
confidence: 99%